2020
DOI: 10.1016/j.arcmed.2020.04.020
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Interventions for COVID-19 Prevention

Abstract: The recent outbreak of CoVID-19 is declared as a global public health emergency of international concern by the World Health Organization (WHO). A fresh figure of 2268011 positive cases and 155185 death records (till April 18 th 2020) across the worldwide signify the severity of this viral infection. CoVID-19 infection is a pandemic, surface to surface communicable disease with a case fatality rate of 3.4% as estimated by WHO up to March 3 rd 2020. Unfortunately, the current unavailability of an effective anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
229
0
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(270 citation statements)
references
References 45 publications
0
229
0
19
Order By: Relevance
“…Depending upon the nature of the surface, pH, temperature and relative humidity of the surrounding, virus persistence time varies from 1–9 days. The highly risk exposed surface areas need to be cleaned frequently with a suitable disinfectant ( Pradhan et al, 2020 ). Person-to-person transmission contributes a major part to make this infection pandemic.…”
Section: A Sociodemographic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending upon the nature of the surface, pH, temperature and relative humidity of the surrounding, virus persistence time varies from 1–9 days. The highly risk exposed surface areas need to be cleaned frequently with a suitable disinfectant ( Pradhan et al, 2020 ). Person-to-person transmission contributes a major part to make this infection pandemic.…”
Section: A Sociodemographic Characteristicsmentioning
confidence: 99%
“…There are many different hydroalcoholic hand sanitizer formulas available on the market with variable effectiveness. Misinformation and inadequate choice of an effective product by the population means that the measure may be ineffective in protecting the general population which does not guarantee the effectiveness of the use of these agents as a preventive measure ( Pradhan et al, 2020 ). Transmission through contaminated hands share a major contribution to the spread of COVID-19 infection.…”
Section: A Sociodemographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Personal preventive measures towards COVID-19, including proper handwashing, appropriate facemask use, and respiratory hygiene practices (cough etiquette), are particularly important [18][19]. Clinical experts recommend that proper handwashing technique involve 7 steps and last at 20 seconds [23][24][25], and it is recommended to cover nose and mouth with tissue or and an elbow rather than hands when coughing or sneezing [17,[21][22][23][24][25][26]. However, our research revealed that the majority of participants had incorrect information on handwashing technique and respiratory hygiene practice ( Table 2, q11 and q12).…”
Section: Discussionmentioning
confidence: 99%
“…Based on above research, personal protective measures, personal hygiene, and appropriate social distance remain the most viable options for prevention among children [6,19,[21][22][23][24][25][26]. In recent months schools around the world have gradually begun to reopen, including in most provinces in China, causing many parents to fear for their children's safety in the midst of a pandemic.…”
Section: Introductionmentioning
confidence: 99%